Sex Hormones Are Associated With Rumination and Interact With Emotion Regulation Strategy Choice to Predict Negative Affect in Women Following a Sad Mood Induction - Graham, Bronwyn M.; Denson, Thomas F.; Barnett, Justine; Calderwood, Clare; Grisham, Jessica R. (Frontiers in Psychology, 2018)
Women are particularly vulnerable to anxiety and depressive disorders. This greater vulnerability has been partly attributed to post-pubertal sex hormone fluctuations, estradiol and progesterone, as well as gender-specific tendencies to engage in maladaptive forms of emotion regulation, particularly rumination. To date, no research has investigated whether sex hormones are associated with emotion regulation in women. In the present study, 61 women participated in a sad mood induction task, involving the viewing of an emotive film. Negative affect was assessed immediately and following recovery, along with self-reported use of rumination, reappraisal, and suppression. Serum levels of estradiol and progesterone were assessed through a blood sample taken at the end of the experiment. Regression analyses were used to examine the relationship between serum hormones and self-reported emotional regulation strategy use, and between serum hormones and the impact of these strategies on negative affect. Estradiol levels positively predicted rumination, but not suppression or reappraisal use. Moreover, estradiol and progesterone interacted with emotion regulation strategies to predict negative affect following the sad mood induction. Reappraisal was associated with greater negative affect only in women with high estradiol, and in women with high progesterone. Conversely, rumination was associated with greater negative affect only in women with low estradiol. Together, these results suggest that sex hormone concentration may be an endogenous contextual factor that is associated with the selection and consequences of emotion regulation strategies in women.